Tinjauan Islam terhadap Kejahatan Ekonomi - Meirison, Meirison (Islamic Criminal Law Study Program, Faculty of Sharia and Law, Sunan Ampel State Islamic University Surabaya, Surabaya, East Java, Indonesia., 2019)
The understanding of crime in the Islamic economic perspective, in various dimensions both prevention, curative prevention and rehabilitation have differences with other economic systems. But there are still many similarities in the viewpoints of economic crime that exist such as the foundation, the purpose of evil. Prevention of crime is related to the awareness of the individual, the community, the source of the law applied, the readiness of the community in the application of the law. Implementation of the law as a whole is a state obligation with all legal instruments that exist in the country, such as apparatus, judiciary. Inherent inspiration, belief in the unseen is very instrumental in the implementation of the law in Islam. This is almost nonexistent in a secular legal system, especially in the economy. Supervision inherent in the Islamic economic system is very instrumental even has become a key element since the Islamic shari'ah triggered. Islam is the best solution for the prevention of economic crimes of society, nation and state with the existence of a well-documented prevention system. If implemented in earnest then will terbuki Islam can be used as a solution for various kinds of economic crimes.